Determinants of capital structure of government-linked companies in Malaysia / Nur Khasrina Aiman Affandi - Aiman Affandi, Nur Khasrina (Faculty of Business Management, University Teknologi MARA, 2018)
Government-linked companies (GLC) play an important role in the development of the Malaysian economy. However, overall public perception of GLCs in Malaysia has been tainted by the poor performance of key players, namely Malaysia Airline System (MAS) and Proton Holdings Berhad. The capital structure of a firm describes the way in which a firm raised capital needed to establish and expand its business activities. An appropriate capital structure is a critical decision for any business organization including GLCs. The decision is important not only because of the need to maximize returns to various organizational constituencies, but also because of the impact of such decision have on a GLC's ability to deal with its competitive environment. Determining optimal capital structure often being a challenge faced by finance managers. An incorrect financing decision may lead to financial distress and eventually face the bankruptcy if do not managed well. The issue of capital structure has been a subject of major concern for researchers and scholars in recent years. Such concern has brought about a lot of arguments on the subject which led to numerous studies on it in the area of firms finance over the years. Thus, the major focus of this study is to investigate the determinants of capital structure of GLCs in Malaysia. It would help financial managers to improve their financing decisions regarding their financial mix. The data for this study will be collected using secondary data. The dependent variable for this study is Debt Ratio and the independent variables are Firm size, liquidity, profitability and tangibility. This sample of study will consists of 1 1 GLCs listed on Bursa Malaysia Stock Exchange from 2010 to 2016. The firm's capital structure will be analyzed through data gathered from the firms' annual report and Thompson Reuters. Panel Ordinary Least Square (OLS) approach will be applied to test the relationship. The finding of this study indicates that only liquidity and profitability can be used to explain capital structure of GLCs in Malaysia. Liquidity and profitability are significant towards the study at 1% level of significance. Other combinations of independent variables appear to be insignificant in explaining capital structure of GLCs in Malaysia.